Evaluation of the SUNHEART Cardiology Outreach Programme - van Deventer, J.D.; Doubell, A.F.; Herbst, P.G.; Piek, H.; Piek, C.; Marcos, E.; Pecoraro, A.J.K. (SA Heart Journal, 2017)
Introduction: The demand for advanced cardiac care and specialised interventions is on the increase and this results in bottlenecks and increased waiting times for patients who require advanced cardiac care. By decentralising cardiac care, and using a hub-and-spoke model, the SUNHEART Outreach Programme of cardiovascular care aims to improve access to advanced cardiac care in the Western Cape. Tygerberg Hospital is the central hub, with the fi rst spoke being Paarl Hospital. Objective: To determine the value of the SUNHEART Outreach Programme to the public health care system. Methods: An audit of patients accessing the Outreach Programme was performed for the period May 2013 - May 2014 and consequently compared to a historical cohort of patients accessing the health care system during the preceding 6 months, from October 2012 - April 2013. Access to advanced cardiac care was measured in time to initial evaluation, time to defi nitive diagnosis or intervention and patient compliance with appointments. The value to the health care system was also assessed by performing a cost analysis of transport of patients and health care workers, as well as compliance with appointments. We documented the spectrum of disease requiring advanced cardiac care to guide future interventions. Results: Data of 185 patients were included in the audit. Sixty four patients were referred to tertiary care from October 2012 - April 2013 and 121 patients were referred to the outreach facility from May 2013 - May 2014. There was a signifi cant reduction in waiting times with the median days to appointment of the historical cohort being 85 days compared to 18 days in the Outreach Programme cohort (p<0.01). Patient compliance with appointments was signifi cantly superior in the Outreach Programme cohort (90% vs. 56%: p<0.01). Valvular (36.5%) and ischaemic heart disease (35.5%) were the major pathologies requiring access to cardiac care services. Transport costs per patient treated was signifi cantly reduced in the outreach programme cohort (R118,09 vs. R308,77). Conclusion: Decentralisation of services in the form of an Outreach Programme, with a central hub, improves access to advanced cardiac care by decreasing waiting time, improving compliance with appointments and decreasing travel costs.